ANALISIS RASIO LIKUIDITAS DAN RASIO PROFITABILITAS PADA PERUSAHAAN DAERAH AIR MINUM KABUPATEN OGAN KOMERING ULU - Anwar, Yuniarti; Yunsepa, Yopi; Meliyani, Rafiza (Jurnal Ecoment Global, 2020)
Analysis of Liquidity Ratios and Profitability Ratios in Ogan Komering Ulu District Water Supply Company. The formulation of the problem in this study is how liquidity ratios and profitability ratios in Ogan Komering Ulu Regional Water Supply Company? The purpose of this study was to determine the liquidity ratios and profitability ratios in the Regional Water Supply Company of Ogan Komering Ulu Regency.Data analysis techniques used in research using qualitative and quantitative analysis with descriptive methods. The type of data used are primary data and secondary data. From the results of the analysis of the calculation of the level of liquidity of the Regional Water Supply Company of Ogan Komering Ulu Regency during 2014-2017, the average value of the quick ratio was 903.5%, current ratio 1,008.75% and cash ratio of 58.75%. This shows that the company is in good condition because it has exceeded industry standards where the company is able to fulfill its short-term obligations. And the level of profitability over the past four years, namely 2014-2017, is not in a good condition because the calculation of net profit margin, return on investment, and return on equity has a negative value, this is because the company always loses and has not been able to manage the source of funds owned efficient and effective.Keywords: Analysis of financial ratios, liquidity, profitability